The Surface Plasmon Performance of β‐Sn/RGO Hybrid Nanostructure. Issue 6 (24th January 2020) - Wu, Han‐Han; Li, Zi‐Heng; Da, Peng; Cheng, Sheng; Luo, Pai‐Feng; Zhong, Hong‐Hai; Lu, Ying‐Wei
Abstract: A hybrid nanostructure composing of β‐Sn nanoparticles and reduced graphene oxide (RGO) nanosheets is successfully prepared through an effective and low‐cost solvothermal method. Both optical absorption measurements and finite element simulations confirm that the dominating plasmonic resonance frequency of such hybrid nanostructure is tunable in ultraviolet region and the near‐field enhancement effect can be achieved under broadband excitations ranging from ultraviolet to visible, which can be attributed to the coupling between β‐Sn and RGO. In addition, surface enhanced Raman scattering (SERS) determinations and corresponding calculations confirm that such all‐IV hybrid nanostructure can serve as an SERS platform and can be an alternative candidate for other plasmonic applications. Abstract : A hybrid nanostructure composing of β‐Sn nanoparticles and reduced graphene oxide (RGO) nanosheets is prepared. Both optical absorption measurements and finite element simulations confirm that the plasmonic resonance frequency of such nanostructure is tunable and the near‐field enhancement effect can be achieved under broadband excitations, which can be attributed to the coupling between β‐Sn and RGO.